Meeting report of the 2017 KidGen Renal Genetics Symposium - Kushani Jayasinghe; Cathy Quinlan; Zornitza Stark; Chirag Patel; Matthew G. Sampson; Moin Saleem; Andrew J. Mallett; on behalf of the KidGen Collaborative (Human Genomics, 2018)
Abstract The 2017 KidGen Renal Genetics Symposium was held at the Royal Children’s Hospital and Murdoch Children’s Research Institute, Melbourne, from 6 to 8 December 2017. This meeting addressed clinical, diagnostic, and research aspects of inherited kidney disease. More than 100 clinicians, researchers, and patient representatives attended the conference. The overall goal was to improve the understanding and direction of genomics in renal medicine in Australia and discuss barriers to the use of genomic testing within this area. It also aimed to strengthen collaborations between local, state, and global research and diagnostic and clinical groups.